PENGARUH CAPITAL STRUCTURE TERHADAP PROFITABILITAS UJI MODEL KUADRATIK PADA PERUSAHAAN SEKTOR AGRIKULTUR YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Cellina Cellina; Putu Anom Mahadwartha; Liliana Inggrit Wijaya (Perpustakaan Universitas Surabaya, 2018)
This study aims to analyze the effect of capital stucture towards profitability using return on assets (ROA) as a proxy in agriculture sector companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2016. This research uses quantitative approach with quadratic regression analysis model. This study uses sample of firms which are listed on agriculture sector in IDX on 2012- 2016. The number of final samples used in this study were 15 business entities with 75 observations. The study findings suggest that the TD variables have positive and significant effect towards profitability, while the TD2variables have negative and significant effect towards profitability in agriculture sector companies BEI on the period 2012-2016.